Case Report: Hydronephrosis and nephrogenic adenoma secondary to Stevens-Johnson syndrome - Wang, Chuan; Huang, Yidong (Frontiers in Pharmacology, 2025)
IntroductionStevens–Johnson syndrome is a rare, severe cutaneous adverse reaction. There is a lack of literature reporting the complications of the bladder and ureter caused by Stevens–Johnson syndrome. In this case, we describe a 10-year-old boy with hydronephrosis and nephrogenic adenoma secondary to Stevens–Johnson syndrome.Case descriptionA boy was admitted to our hospital after a CT scan revealed bilateral hydronephrosis. He had been diagnosed with Stevens–Johnson syndrome earlier. Ureteroscopy and bilateral retrograde ureteral stenting were performed. After the guidewires were introduced, a mass of mucosal debris gushed from the ureteral orifices. Biopsy findings of the mucosal lesions were consistent with nephrogenic adenoma. Two months later, ultrasonography revealed worsening hydronephrosis. The double-J stents were removed. Follow-up ultrasonography showed an improvement in the hydronephrosis.ConclusionStevens–Johnson syndrome is a life-threatening mucocutaneous disorder. Ureteral obstruction and hydronephrosis can be caused by mucosal debris in patients with Stevens–Johnson syndrome, which may contribute to and exacerbate renal dysfunction. Nephrogenic adenoma can occur to patient with Stevens–Johnson syndrome as a result of the proliferation of implanted renal tubular cells. Routine ultrasonography should be conducted to monitor the urinary system.